Whole-genome sequencing confirms Shigella flexneri infection in a child with shock and suspected multisystem inflammatory syndrome in children: A case report - Sheridan J.C. Baker; Laura K. Erdman; Donald Brody Duncan; Tania Cellucci; Candy Rutherford; Marek Smieja; Cheryl Main; Jeffrey M. Pernica; Andrew G. McArthur (IDCases)
Background: Differentiating severe systemic inflammatory syndromes from sepsis can be challenging. The diagnostic process may be further complicated by concurrent infection and hyperinflammation, with important management implications. We report a child with suspected multisystem inflammatory syndrome in children, who was unexpectedly diagnosed with Shigella gastroenteritis. Case presentation: A previously healthy 6-year-old boy acutely presented with fever, vomiting, diarrhea, fluid-refractory shock, cardiac dysfunction, biochemical inflammation, and coagulopathy. He fulfilled diagnostic criteria for multisystem inflammatory syndrome in children, including SARS-CoV-2 exposure 8 weeks prior. He received both antibiotics and pulsed intravenous methylprednisolone, with rapid improvement. Stool molecular testing using a lab-developed multiplex qPCR assay revealed Shigella flexneri infection, confirmed by culture, MALDI-TOF mass spectrometry, and whole-genome sequencing. Serologic testing confirmed prior infection by the SARS-CoV-2 virus. The child fully recovered. Immunological investigations were normal. The case was investigated by the Public Health Department, but the source of Shigella infection was not identified. Conclusions: This case underscores the importance of systematic microbiological workup in suspected systemic inflammatory syndromes, to identify infections that are treatable and of public health relevance. Given the rarity of Shigella septic shock in immunocompetent individuals, this case raises the possibility that recent SARS-CoV-2 infection led to immune dysregulation and exaggerated inflammatory responses to Shigella. It also demonstrates the utility of molecular testing for rapid diagnosis and confirmation of gastrointestinal infection.